If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(3x+2)=3x-30
We move all terms to the left:
3(3x+2)-(3x-30)=0
We multiply parentheses
9x-(3x-30)+6=0
We get rid of parentheses
9x-3x+30+6=0
We add all the numbers together, and all the variables
6x+36=0
We move all terms containing x to the left, all other terms to the right
6x=-36
x=-36/6
x=-6
| C=0.75x+15 | | -y=10+4y | | -5n+4=34 | | -46=r-3.3 | | 7k-14=24 | | 1.1/2h=4 | | (1/4)x-6=4 | | 8y-4+3(y+7)=6y-y(y-3) | | 4(6x-9)=-3(12-8x) | | -22x+1+11x=-8x-26 | | -6-5r=-94 | | (-1+-1/2)h=4 | | T=5c+112 | | 11-3x=49 | | 23x-5=3 | | 2×y-18.2=3.8 | | (2x=1)(3x+2) | | 3(1+5n)-2=-104 | | (-1+1/2)h=4 | | 200=2n+5n | | 15x−15=3x+45 | | 2n*5n=200 | | x^2+20x-2600=0 | | -84=-4(4x+1) | | 6(1-4x)=8x+38 | | 60p=20 | | 6h+8-3h+2=15 | | 3x²-9x+6=0 | | -8(w+9)=-8 | | 2/3-2x=6 | | 12x+6=12x-4 | | 6x-4=-(32x-2) |